Evaluation of changes in objective visual quality based on tear film stability after SMILE surgery - Liao, Tao; Li, Lili; Wei, Diefeng; Mao, Hejuan; Huang, Yanyan; Lu, Pengfei; Zhong, Dedong; Lu, Haiyan; Huang, Huiyao; Chen, Qi (Frontiers in Medicine, 2025)
PurposeThis study aimed to evaluate changes in visual quality among myopic patients with varying tear film stability after small incision lenticule extraction (SMILE) using the Optical Quality Analysis System (OQAS II).MethodsThis prospective study analyzed 141 patients who underwent SMILE surgery, selecting the right eye of each patient for analysis. Objective visual quality and tear film stability were assessed using the OQAS II preoperatively and at 1 week, 1 month, and 3 months postoperatively. Refractive error and uncorrected visual acuity were measured at the same time points. At the 1-week follow-up, all patients completed a visual quality questionnaire and underwent tear film break-up time (TBUT) measurement. These assessments were conducted to evaluate the correlation between subjective visual perception and objective visual quality, as well as to examine the relationship between the two methods of tear film evaluation.ResultsNo significant differences in UDVA or postoperative spherical and equivalent spherical values were observed between groups at any postoperative time point (p > 0.05). At 1 week and 1 month post-surgery, both groups exhibited elevated Objective Scatter Index (OSI) and Mean OSI values, while OV100%, OV20%, OV9%, MTF cutoff, and Strehl ratio (SR) decreased compared to preoperative levels (all p < 0.05). By 3 months post-surgery, all objective visual quality parameters in the tear film stability group returned to preoperative levels (p > 0.05). In contrast, in the instability group, only SR remained unchanged, while other parameters significantly differed from baseline (p < 0.05). Positive correlations were found between OSI values and both foggy vision and glare at 1 week postoperatively in both groups. TF-OSI values positively correlated with blinking frequency and visual fluctuations. OV100% values at all preoperative and postoperative time points did not effectively predict subjective visual acuity.ConclusionTear film instability negatively impacts visual quality recovery and prolongs corneal healing time after SMILE surgery. However, it does not cause short-term refractive regression. OV100% shows limited predictive ability for visual acuity. A significant correlation exists between objective visual quality and subjective perception. The OQAS II system is a valuable tool for assessing tear film stability and objective visual quality in refractive surgery patients.